2018
DOI: 10.1016/j.robot.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Learning a bidirectional mapping between human whole-body motion and natural language using deep recurrent neural networks

Abstract: Linking human whole-body motion and natural language is of great interest for the generation of semantic representations of observed human behaviors as well as for the generation of robot behaviors based on natural language input. While there has been a large body of research in this area, most approaches that exist today require a symbolic representation of motions (e.g. in the form of motion primitives), which have to be defined a-priori or require complex segmentation algorithms. In contrast, recent advance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…In addition, it has been proven that a GAN has a unique solution, in which G captures the distribution of the real data and D does not distinguish the real data from the data generated from G [8]. Thanks to these features of GANs, our experiment also shows that GANs can generate more realistic action than the previous work [5].…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…In addition, it has been proven that a GAN has a unique solution, in which G captures the distribution of the real data and D does not distinguish the real data from the data generated from G [8]. Thanks to these features of GANs, our experiment also shows that GANs can generate more realistic action than the previous work [5].…”
Section: Introductionmentioning
confidence: 71%
“…The result shows that our generative model synthesizes the human action sequence that is more similar to the data. Although the network presented in [5] also generates the action as the ballet player with both arms open, it is shown that the action sequence synthesized by our network is more natural and similar to the data.…”
Section: Comparison With [5]mentioning
confidence: 85%
See 3 more Smart Citations